The Importance Of Understanding The Meaning of Mutasyabih Verses To Prevent Wahabiya Understanding in Madrasah Tsanawiyah Al-Fauzi Cinta Rakyat Percut Sei Tuan - Deli Serdang Sumatera Utara - Laila Rahimah Harahap; Zulkifli Nasution (Jurnal Eduslamic, 2023)
This journal discusses the Importance of Understanding the Interpretation of Mutasyabih Verses to Prevent Wahabiyah Understandings at MTs Al-Fauzi Cinta Rakyat with the aim of analyzing how important understanding the meaning of mutasyabih verses is and what effect they have on education. This type of research is Qualitative Research with a descriptive data presentation model and the research instruments are observations and interviews with the principal, deputy principal and several students. Al-Quran consists of two types of verses, namely muhkam verses whose meaning is clear and mutasyabih verses whose meaning is not clear so this makes the scholars have two views, namely the salaf scholars and khalaf scholars, there are scholars who support takwil on verses mutasyabih (ulama' khalaf) and there are also ulama' who reject the existence of takwil on mutasyabih verses (ulama' salaf). Lately there have been many wahabiyah teachings spreading in the name of themselves as salafi and saying that Allah resides in the Throne. The results of this study found that understanding the interpretation of the meaning of mutasyabih verses is very important in the world of education in order to prevent Wahhabism and errors in belief.